2017
DOI: 10.1093/jcr/ucx057
|View full text |Cite
|
Sign up to set email alerts
|

It’s Too Pretty to Use! When and How Enhanced Product Aesthetics Discourage Usage and Lower Consumption Enjoyment

Abstract: Marketers invest a lot of resources in product aesthetics and design, but does this strategy always lead to favorable consumer outcomes? While prior research suggests enhanced aesthetics should have a uniformly positive influence on pre-usage evaluations and choice, the present research examines the downstream effects of nondurable product aesthetics on consumption behavior and post-consumption affect. First, we document an inhibiting effect of aesthetics on actual consumption. We find that highly aesthetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 54 publications
1
87
3
2
Order By: Relevance
“…Our findings that certain types of effortful beauty work are viewed negatively contrast with prior work that largely reveals consumers' appreciation of the effort that others put into specific products or displays (Kruger et al 2004;Morales 2005). Recent work on nondurable goods (e.g., cupcakes, napkins) has even shown that people value beautiful products precisely because of the effort that went into creating them (Wu et al 2017). Interestingly, people have the opposite intuitions when considering the effort exerted to achieve an attractive physical appearance because such effort is seen as dishonest.…”
Section: Theoretical Contributionscontrasting
confidence: 65%
See 1 more Smart Citation
“…Our findings that certain types of effortful beauty work are viewed negatively contrast with prior work that largely reveals consumers' appreciation of the effort that others put into specific products or displays (Kruger et al 2004;Morales 2005). Recent work on nondurable goods (e.g., cupcakes, napkins) has even shown that people value beautiful products precisely because of the effort that went into creating them (Wu et al 2017). Interestingly, people have the opposite intuitions when considering the effort exerted to achieve an attractive physical appearance because such effort is seen as dishonest.…”
Section: Theoretical Contributionscontrasting
confidence: 65%
“…Still, research has not investigated how effort related to improving one's appearance is perceived or its implications for consumption. While prior work has focused largely on consumers' appreciation of their own and others' effort pertaining to products, gifts, and displays (Cutright and Samper 2014;Kruger et al 2004;Morales 2005;Moreau, Bonney, and Herd 2011;Wu et al 2017), we examine how and why exerting effort on beauty work can negatively affect judgments of moral character.…”
Section: Beauty Work and Effortmentioning
confidence: 99%
“…We measured the aesthetic effect of the Buddhist symbols using a 6-item Likert scale adapted from the related literature [115]. In this study, the visual aesthetics were emphasized (''This Buddhist symbol looks attractive/ beautiful/ artistic/ pretty/ aesthetically appealing/ arousing'', 1 = Strongly In order to control for these co-founding factors, we ran two pilot studies to explore whether the meaning of the adapted symbol is consistent with the original one and whether this symbol could elicit higher happiness compared with the control group.…”
Section: Aesthetic Effect Of the Buddhist Symbolsmentioning
confidence: 99%
“…We measured the aesthetic effect of the Buddhist symbols using a 6-item Likert scale adapted from the related literature [115]. In this study, the visual aesthetics were emphasized ("This Buddhist symbol looks attractive/ beautiful/ artistic/ pretty/ aesthetically appealing/ arousing", 1 = Strongly Disagree, 5 = Strongly Agree).…”
Section: Aesthetic Effect Of the Buddhist Symbolsmentioning
confidence: 99%
“…First of all, three major streams of relevant research were reviewed: the theoretical work of the centrality of visual aesthetics and perceived aesthetics from a psychological perspective (Workman and Caldwell 2007;Bloch et al 2003;Wu et al 2017;Lee and Koubek 2010;Hekkert et al 2017), the explicit aesthetics of Buddhist items (Inada 1994;Schopen 2006), as well as religious aesthetics literature, especially the religious aesthetics of items and symbols from a sensory perspective (Meyer 2010(Meyer , 2006Prohl 2010). Then, 42 college students at a major university in the eastern part of China were recruited to describe their experience and feelings when viewing Buddhism items or symbols.…”
Section: Items Generationmentioning
confidence: 99%